Análisis de la complejidad perceptivo-motriz y psicológica del penalti en el fútbol. [Analysis of the perceptual-motor and psychological complexity of the soccer penalty kick]. - José A. Navia; Luis M. Ruiz (Ramón Cantó Alcaraz, 2014)
A common though among soccer professionals is that penalties are a lottery, despite the existence of numerous empirical works that prove the opposite. An ample review about soccer penalty kick studies is presented in the current paper. The document is structured in three main sections: how to improve goalkeeper's success probability, how to improve kicker's success probability, and how to improve team's success probability in a penalty shootout. Within each of the three sections, it is review how three of the factors that influence penalty kick performance interact. That is, perceptual-motor skills, information from players' previous performance and psychological factors. A common feature of the entirely reviewed studies is the emphasis with which authors strongly suggest training penalty kicks. Therefore, it can be concluded that soccer penalty kicks are not a lottery but should be appropriately trained in order to improve the achievements. In this regards, this paper may result helpful when programming training since main research findings concerning soccer penalty kick are displayed.